Handbook of environmental and sustainable finance - Ramiah, Vikash; Gregoriou, Greg N. 1956- (Academic Press, an imprint of Elsevier, 2016)
The use of financial concepts and tools to shape development is hardly new, but their recent adoption by advocates of sustainable environmental management has created opportunities for innovation in business and regulatory groups. The Handbook of Environmental and Sustainable Finance summarizes the latest trends and attitudes in environmental finance, balancing empirical research with theory and applications. It captures the evolution of environmental finance from a niche scholarly field to a mainstream subdiscipline, and it provides glimpses of future directions for research. Covering implications from the Kyoto and Paris Protocols, it presents an intellectually cohesive examination of problems, opportunities, and metrics worldwide